1988
DOI: 10.12930/0271-9517-8.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Engineering Students

Abstract: The following study compared academic achievement traits of men and women to determine why women are underrepresented in certain curricula, especially engineering. Math-related attitude and anxiety factors were examined via a questionnaire, and a number of ACT test scores were studied. The results may surprise some readers and should be of interest to all advisors working with science and/or engineering students, especially women students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Three studies conducted at three different universities found no significant differences in the grades earned by men and women. 6,8,12 Once again, though, it is not clear how generalizable this finding is given that only three universities have been investigated.…”
Section: Performancementioning
confidence: 97%
See 1 more Smart Citation
“…Three studies conducted at three different universities found no significant differences in the grades earned by men and women. 6,8,12 Once again, though, it is not clear how generalizable this finding is given that only three universities have been investigated.…”
Section: Performancementioning
confidence: 97%
“…of mathematics, science, and engineering) • encouragement (e.g., females receive less encouragement to pursue engineering than males). [5][6][7][8][9] Women who enter engineering programs, then, are somewhat atypical in the sense that they are more interested in engineering than most of their peers and believe that they could do well in an engineering program. Investigations into the backgrounds of these women reveal that their high levels of interest and self-confidence were fostered by unusually supportive environments at home and school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stu dent characteristics which have an impact on advising satisfaction were identified as department affiliation (Rosenberg, 1969), student grade point avera# (Morehead & Johnson, 1964), age of the student (Dewey, 19W;Grites. 1982;Kasworm, 1980;Kuh & Sturgis, 1980;Reehling, 1980; Sauders S Erving, l%4), and student gender (Ourio & Kildow, l%0;Rossman, 1967Rossman, , 1968Whigham, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Research on retention of men and women engineering students revealed greater attrition among women, but advising was reported as having no ap parent effect in the decision of the student to withdraw (Durio 4 Kildow, 1980;Whigham, 1988).…”
mentioning
confidence: 99%
“…According to s o m e a u t h o r s ( D u r i o & Kildow, 1980;Rossman, 1968;Whigham, 1988) gender may be related to higher retention rates in specific disciplines and t o student use of the assigned faculty advisor. Relationships among student…”
mentioning
confidence: 99%